MDCT in the Differentiation of Adrenal Masses: Comparison between Different Scan Delays for the Evaluation of Intralesional Washout. (7th March 2013) - Angelelli, Giuseppe; Mancini, Maria Elisabetta; Moschetta, Marco; Pedote, Pasquale; Pignataro, Pasquale; Scardapane, Arnaldo
Abstract : Purpose . To evaluate the accuracy of the washout in the differential diagnosis between adenomas and nonadenomas and to compare the obtained results in delayed CT scans at 5, 10 and 15 minutes. Methods . Fifty patients with adrenal masses were prospectively evaluated. CT scans were performed by using a 320-row MDCT device, before and after injection of contrast material. In 25 cases, delayed scans were performed at 5′ and 10′ (group 1), while in the remaining 25, at 5′ and 15′ (group 2). Absolute and relative wash-out percentage values (APW and RPW) were calculated. Results . Differential diagnosis between adenomas and nonadenomas was obtained in 48/50 (96%) cases, with sensitivity, specificity, and accuracy values of 96%, 95%, and 96%, respectively. In group 1, APW and RPW values were, respectively, 69.8% and 67.2% at 5′ and 75.9% and 73.5% at 10′ for adenomas and 25.1% and 15.8% at 5′ and 33.5% and 20.5% at 10′ for nonadenomas. In group 2, APW and RPW values were 63% and 54.6% at 5′ and 73.8% and 65.5% at 15′ for adenomas and 22% and 12.5% at 5′ and 35.5% and 19.9% at 15′ for nonadenomas. Conclusions . The evaluation of the wash-out values in CT scans performed at 5′, 10′, and 15′ provides comparable diagnostic results. CT scans performed at 5′ are, therefore, to be preferred, since they reduce the examination time and patient discomfort.